How does ESG performance reduce financial risk — Evidence from China listed companies - Xu, Ruhui; Zhong, Jun; Huang, Ting (Transactions on Economics, Business and Management Research, 2024)
The concept of sustainable green development has attracted considerable interest, with a diverse range of stakeholders from the environmental, social, and corporate governance (ESG) sectors demonstrating a keen interest in it. This paper presents an experimental investigation into the effect of ESG performance on financial analysis, utilising annual data from a-share listed businesses between 2010 and 2022. The findings indicate that financial risk can be reduced by strong ESG performance. The influence mechanism study found that by easing financing limitations, enhancing corporate ethical culture, and raising the bar for corporate innovation, companies with strong ESG performance primarily lower their financial risk. The results of the heterogeneity study indicated that smaller, non-state-owned, and eastern area businesses had better results when it came to lowering financial risk. Through the empirical test of ESG performance on financial risk, this paper offers insights for enterprises and investors to prioritize ESG performance and for government departments to enhance ESG incentive policies.